The Influence of Net Profit Margin, Current Ratio and Debt to Equity Ratio on Company Value With Dividend Policy as an Intervening Variable in Retail Subsector Companies for the 2012-2019 Period - Deni Sunaryo (Edumedia Solution, 2022)
The purpose of this study is to determine the effect of Net Profit Margin, Current Ratio and Debt to Equity Ratio to Firm Value with Dividend Policy as an Intervening variable which shows the dissimilarity of results in previous studies. This research uses the object of Retail sub-sector companies in Southeast Asia for the period 2012-2019. The sampling method used in this study used purposive sampling technique and obtained 19 companies with a total of 152 samples.The analysis technique used is descriptive test analysis, classical assumption test, coefficient of determination test (R2), multiple linear regression analysis, t test, F test, path analysis and sobel test. The results of the study partially concluded that the Net Profit Margin had a significant effect on the Price Earnings Ratio. Current Ratio and Debt to Equity Ratio have no significant effect on Price Earnings Ratio. Simultaneously concluded that the Net Profit Margin, Current Ratio and Debt to Equity Ratio have a significant effect on the Price Earnings Ratio. Net Profit Margin has no significant effect on Earnings Per Share. Current Ratio and Debt to Equity Ratio have a significant effect on Earnings PerShare. Price Earnings Ratio has no significant effect on Earnings PerShare. The results of the study can be concluded that Earnings per Share cannot mediate the effect of Net Profit Margin, Current Ratio and Debt to Equity Ratio on Price Earnings Ratio.